THE ROLE OF CASES, REGULATIONS, POLICIES, GUIDELINES AND LEGISLATIONS ON THE E-COMMERCE SECURITY - Jaber, Omar Abdel; Johar,; MGM,; Al-masaeed, Sultan (International Journal of Psychosocial Rehabilitation, 2020)
As e-business becomes part of an everyday experience of the majority of people who tends to be risk- adverse, security become crucially important(E-Commerce & Development Report, 2003). Internet security problems take multiple forms: spam, viruses, web squatting, fraud, copyright violation, denial of service, unauthorized entry into corporate or personal computers and networks(and theft or manipulation of the information stored in them), privacy infringements, fraud and harassment. The following issues will be examined with reference to the purpose of this study: E-commerce policies, Computer crimes, Electronic Privacy and Authentication & Encryption. It is proposed that these three(3) principles are examined in order to tackle security and safety in e-commerce. These principles are derived from the review of all the legislations, cases, guidelines, policies and regulations in this paper. All these principles are complementary to each other. Self-regulation, Ethics, Enforcement. Security and safety will remain the most vital issues in electronic commerce that will continue to be discussed, examined and addressed. Actions will be continue to be taken by the society to create new laws, technology, methods and processes to increase security and safety in the cyberspace as e-commerce technologies grow. One must not be deterred from electronic commerce just because of these issues. There will always be a downside for everything including electronic commerce. Business growth from this new method of doing business is very lucrative to be abandoned (AlGhamdi, Drew, & Al‐ Ghaith, 2011a; De Silva et al., 2018a; De Silva et al., 2018b; Nikhashemi et al., 2013).